Development of Microfinance Organisations in Vietnam - Thi Thu Hien, Hoang; Creedy, Jonh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 5E, 2020)
The aim of this paper is to examine the development of microfinance in Vietnam from the early 1980s. This provides a particularly interesting case study in view of the large-scale changes that have taken place in the economy over the period, which has experienced the transition from a Central Economic Planning System towards a ‘socialist-oriented market economy’, with increased integration in the world economy. Starting from a framework, or taxonomy, of microfinance organisations, the paper explores how the two main objectives of microfinance organisations - of meeting the economic needs of borrowers and being sustainable - have eventually been met using a diversity of organisational forms.